Olaparib in combination with paclitaxel in patients with advanced gastric cancer who have progressed following first-line therapy (GOLD): a double-blind, randomised, placebo-controlled, phase 3 trial. Issue 12 (December 2017) - Bang, Yung-Jue; Xu, Rui-Hua; Chin, Keisho; Lee, Keun-Wook; Park, Se Hoon; Rha, Sun Young; Shen, Lin; Qin, Shukui; Xu, Nong; Im, Seock-Ah; Locker, Gershon; Rowe, Phil; et al.
Summary: Background: Olaparib combined with paclitaxel has previously shown a significant improvement in overall survival versus placebo plus paclitaxel as second-line therapy in a phase 2 study in Asian patients with advanced gastric cancer, especially in those with ataxia-telangiectasia mutated protein (ATM)-negative tumours. Here, we report the primary efficacy and safety analyses from a subsequent phase 3 trial. Methods: This double-blind, randomised, placebo-controlled, phase 3 study (GOLD) recruited Asian patients aged 18 years or older (≥20 years if Japanese) with advanced gastric cancer that had progressed following, or during, first-line chemotherapy. Patients were randomly assigned (1:1) to receive oral olaparib (100 mg twice daily) plus paclitaxel (80 mg/m 2 intravenously) or matching placebo plus paclitaxel. Randomisation was done through an interactive voice response system and no stratification factors were used. Patients and investigators were masked to treatment allocation. Two co-primary populations were assessed: the overall population of all patients and patients whose tumours were ATM-negative (identified after randomisation, before the data cutoff date, March 28, 2016). The primary endpoint in both populations was overall survival (defined as the time from the date of randomisation until death from any cause before data cutoff); a significant difference was defined as p<0·025. Efficacy was assessed in the intention-to-treat populations and safety in patients who received at least one dose of treatment. This trial is registered withClinicalTrials.gov, numberNCT01924533 (study ID, D081BC00004), and is ongoing but no longer recruiting participants. Findings: Between Sept 3, 2013, and March 28, 2016, 643 patients were enrolled from 58 study sites in hospitals and medical centres in China, Japan, South Korea, and Taiwan. 525 eligible patients were randomly assigned: 263 to receive olaparib plus paclitaxel and 262 to receive placebo plus paclitaxel. 94 patients were determined to have ATM-negative tumours before unmasking for the primary analysis (48 in the olaparib plus paclitaxel group and 46 in the placebo plus paclitaxel group). Overall survival did not differ between treatment groups in the overall patient population (median overall survival 8·8 months [95% CI 7·4–9·6] in the olaparib group vs 6·9 months [6·3–7·9] in the placebo group; HR 0·79 [97·5% CI 0·63–1·00]; p=0·026) or in the ATM-negative population (12·0 months [7·8–18·1] vs 10·0 months [6·4–13·3]; 0·73 [0·40–1·34]; p=0·25). In the overall patient population, the most common grade 3 or worse adverse events in the olaparib plus paclitaxel group were neutropenia (78 [30%] of 262 patients), leucopenia (42 [16%]), and decreased neutrophil count (40 [15%]); in the placebo plus paclitaxel group, they were neutropenia (59 [23%] of 259 patients), leucopenia (27 [10%]), and decreased white blood cell count (21 [8%]). Adverse events with an outcome of death causally related to study treatment (according to investigator assessment) were reported in two patients: liver injury in one patient (<1%) in the olaparib plus paclitaxel group and cardiac failure in one patient (<1%) in the placebo plus paclitaxel group. Interpretation: The GOLD study did not meet its primary objective of showing a significant improvement in overall survival with olaparib in the overall or ATM-negative population of Asian patients with advanced gastric cancer. The study generated informative efficacy and safety data regarding the use of olaparib in combination with a chemotherapeutic agent and provides a foundation for future studies in this difficult-to-treat patient population. Funding: AstraZeneca.